Preschool Teachers’ Perspective Regarding the Urgency of Marine Environmental Education Materials Through Educative Learning Media in Bogor City - Muhammad Rusvendy Doddyansyah; Sri Wulan; Hapidin Hapidin (Universitas Panca Sakti Bekasi, 2023)
Indonesia's wealth of marine natural resources, according to The World Bank, can provide state revenues of up to 27 billion US dollars which meet up to 50 percent of animal protein needs, and employ more than 7 million of its citizens. The situation on the field shows that Indonesian education, from preschool to senior high school, is still directed toward the mainland, not toward the sea, as evidenced by the lack of maritime materials in schools. The Director General of Preschools at the Ministry of Indonesia has issued a maritime materials handbook as a teacher's guide for developing marine environment materials, but teachers are having difficulties because there are no gradual directions and media. Pre-schoolers are not familiar with Indonesia's living and non-living marine natural resources, which have an impact on empowering the sea properly and wisely in the future. The purpose of this study is to explore the perspective of preschool teachers regarding the urgency of marine environmental education materials through the use of educative learning media. Researchers used a qualitative approach with a phenomenological design. The research subjects were five teachers at three schools in Bogor, with data collection in the form of interviews, documentation, and observation. The result of the study shows that from the perspective of preschool educators, many have received environmental or maritime material but have difficulty developing and making suitable media according to the needs of the theme. The study concludes that every preschool teacher tries to apply environmental education to learning, including about the sea. Furthermore, from the perspective of preschool teachers, they need help in several ways; 1) Guidelines include the stages of making a learning plan; 2) Selection of simple but interrelated materials from organisms, professions, to means of transportation; 3) Use of appropriate media and according to the learning theme; and 4) Parental support outside of school as a form of marine environment education habituation.